2007
DOI: 10.1109/tasc.2007.899413
|View full text |Cite
|
Sign up to set email alerts
|

Fine Grained Tantalum for Composite ${\rm Nb}_{3}{\rm Sn}$ Superconductor Diffusion Barrier Sheet

Abstract: Poor deformation behavior of commercial polycrystalline Ta sheet used for Sn diffusion barriers in Nb 3 Sn composite superconductors leads to the use of more Ta than may be necessary in these conductors, and to strand fracture during wire drawing. These problems arise because of nonuniform deformation of the Ta layer when co-drawn with Cu. The origin of the problem resides in the microstructure of the Ta and the code formation mechanics of relatively strong BCC Ta with weaker and more ductile adjacent FCC Cu. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…As reported previously [1][2][3], an impediment to the efficient use of Ta as a diffusion barrier material in Nb 3 Sn superconductors is poor co-deformation behavior of commercial 325 This article is copyrighted as indicated in the article. Reuse of AIP content is subject to the terms at: http://scitation.aip.org/termsconditions.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…As reported previously [1][2][3], an impediment to the efficient use of Ta as a diffusion barrier material in Nb 3 Sn superconductors is poor co-deformation behavior of commercial 325 This article is copyrighted as indicated in the article. Reuse of AIP content is subject to the terms at: http://scitation.aip.org/termsconditions.…”
Section: Introductionmentioning
confidence: 84%
“…The ECAE processed Ta billets were rolled into sheet following procedures reported previously [2]. Individual Ta sheets prepared by different processing schedules were incorporated into separate Cu-Ta composites Table 1 indicates the conditions of the sheets prior to assembly.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the grain size was refined significantly due to the increase in hardness, but some coarse grains appeared with increasing the numbers of rotations. Mathaudhu et al produced a fine grained Ta via multi-pass equal channel angular extrusion (ECAE) process [ 17 ]. It was concluded that the refined nano-grains with the size of 100–400 nm was found to be beneficial for Nb 3 Sn superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…The Nb and Nb7.5wt.%Ta has also been wrapped with a Ta barrier to reduce the tendency of the Sn to go into the Cu matrix but these sub-elements could not be made into restacks of more than 19-sub-elements. The low ductility of the Ta was believed to be the cause of the wire breakage and this approach requires a more ductile Ta such as that being developed by Shear Form Inc, (SFI), Bryan, TX, using Equal Channel Angular Extrusion (ECAE) [14].…”
mentioning
confidence: 99%